An innovation in Career Guidance in Higher education: Effectiveness and Sustainability of Institutionalization of Service Learning in the University of Colombo - Udagama, P.; Wijayanama, C.; Vithanapathirana, M. (My University, 2019)
Service learning, a structured learning experience, blends voluntary community service with academic learning. This paper reports the innovation which fostered reflection and assessment leading to deeper understanding of course content and civic engagement, applying academic knowledge, critical thinking and problem solving skills, through collaborative partnership between University, corporates and community. To date, this remains the only credit based Service Learning course offered by a Sri Lankan university. The pilot programme launched by the Career Guidance Unit (CGU), Faculty of Science, and University of Colombo in 2012, was developed as a design-based research. Following intensive literature review and discussion with teaching faculty, CGU obtained formal approval for the integration of “Service Learning” to the Bachelor of Science curriculum. In the pilot study, the faculty collaborated with three corporate sponsors through three service learning projects connecting with academic learning goals. Faculty project coaches, corporate project partners, and student groups collaborated in project planning and implementation. Evaluation was based on interviews, written reports, and presentations. The programme has matured and is continued to-date with strongly encouraging outcomes of this pioneering exercise. Service learning is recommended as an effective pedagogy for the Sri Lankan university system, capable of transforming traditional teaching and learning practices.
Keywords: Service learning; higher education; career guidance; tripartite collaboration; social innovation; design-based